Marine mammals harbor unique microbiotas shaped by and yet distinct from the sea - Elisabeth M. Bik; Elizabeth K. Costello; Alexandra D. Switzer; Benjamin J. Callahan; Susan P. Holmes; Randall S. Wells; Kevin P. Carlin; Eric D. Jensen; Stephanie Venn-Watson; David A. Relman (Nature Communications, 2016)
Little is known about the microbiota of marine mammals, despite the crucial ecological roles played by these animals. Here, Bik et al. describe the bacterial communities associated with various body sites in dolphins and sea lions, as well as the microbiota of their dietary fish and adjacent seawater.